Interdisciplinary Clinical Management of Streptococcal Pharyngitis: Diagnostic, Therapeutic, and Preventive Perspectives in Respiratory Care, Nursing Practice, Pharmacy, and Radiology - Alabdulwahed, Shoug Abdullah; Horiah Eid Salim Alotibi; SALIHAH MOFAREH; Qassim Hassan Albahrani; Madinah Ali Albutayyan; Mohammad Johar Alanbar; Aziz Saleh Albalwi; Fouz Thiaby Yahya Hakami; Firoz Thiaby Yhia Hakami; Hussain Jawad Ahmed Alhadhari; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Streptococcal pharyngitis, caused by Group A Streptococcus (GAS), is a common respiratory infection predominately affecting children and adolescents, with lower incidence among adults. It remains a significant clinical concern due to its transmissibility, symptom burden, and potential for suppurative and nonsuppurative complications. The overlap of bacterial and viral presentations frequently challenges diagnostic accuracy, contributing to unnecessary antibiotic use. Aim: This interdisciplinary review aims to synthesize current evidence regarding the diagnosis, management, prevention, and interprofessional collaboration required for optimal care of streptococcal pharyngitis. Methods: A comprehensive analysis of epidemiological data, diagnostic criteria, clinical decision rules, antimicrobial guidelines, and multidisciplinary care recommendations was extracted and synthesized from the provided article. Results: The review highlights key epidemiological trends, including peak incidence in children and reduced prevalence in adults. Evidence demonstrates that clinical examination alone is insufficient for diagnosis; validated scoring systems (Centor, McIsaac) combined with rapid antigen detection testing improve accuracy and reduce unnecessary antibiotic use. Penicillin and amoxicillin remain first line therapy, with alternatives guided by allergy profile and local resistance patterns. Strategies for preventing complications and transmission include strict hand hygiene, adherence to therapy, and appropriate exclusion from school or work. Interprofessional collaboration—uniting physicians, nurses, pharmacists, and laboratory teams—enhances diagnostic precision, treatment adherence, patient education, and public health outcomes. Conclusion: Effective management of streptococcal pharyngitis requires accurate diagnostic testing, evidence based antibiotic selection, and coordinated interprofessional care. Preventive measures and patient education remain essential to reducing disease burden and complications.